Teacher’s Strategies for Teaching English Vocabulary to Slow Learner in Inclusive Classroom - Tuti Alawiyah Ramadani Nasution; Siti Ismahani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to identify teachers’ strategies for teaching English vocabulary to slow learners in inclusive classrooms, as well as to uncover the challenges faced and the solutions implemented. Using a descriptive qualitative approach, data were collected through classroom observations, teacher interviews, and documentation, and then analyzed thematically. The results of the study revealed six strategies used by teachers: repetition, Total Physical Response (TPR), explicit phonics instruction, the use of visual media, games, and task differentiation. The challenges that emerged included a lack of parental support and difficulties with the pronunciation of consonant clusters, which teachers addressed through the Family Literacy Movement (GLK) and a step-by-step phonics approach. These findings underscore the importance of multisensory and adaptive strategies in vocabulary learning in inclusive classrooms, while also providing practical guidance for English teachers.